(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2016)
Vitamin K deficiency may cause unexpected bleeding sometimes severe one into the brain in previously apparently healthy neonates, known as Vitamin K Deficiency Bleeding (VKDB) of newborn. Vitamin K prophylaxis in the newborn continues to be a worldwide health concern. A single intramuscular prophylactic dose (0.5 to 1 mg) of vitamin K within first 6 hrs of delivery is preferable till date in preventing VKDB. This observational study was carried out to see the current practices of vitamin K prophylaxis in newborn in different health care centers of a metropolitan area of Chittagong in Bangladesh from July 2013 to December 2013. Total 103 cases were enrolled in this study among them in 82 (79.61%) cases vitamin K prophylaxis was administered after initiation of breast feeding and in 21 (20.39%) cases it was offered before initiation of breast feeding. In 89 (86.40%) cases route of administration was oral whereas in 2 (1.94%) and 12 (11.65%) cases routes were intramuscular and intravenous respectively. In this study it is observed that most of the neonates received vitamin K prophylaxis orally, which is not the currently recommended route to prevent VKDB. So awareness should be promoted in this regard. JCMCTA 2016 ; 27 (1) : 46 - 50